Serangan Kumbang Badak pada Tanaman Kelapa di Desa Jati Mulya Kecamatan Wonosari Kabupaten Boalemo - Zhahrani, Eksanty Mustika; Lihawa, Mohamad; Musa, Nikmah (Jurnal Agro Industri Perkebunan, 2024)
Pest organisms threaten plant cultivation by disrupting plant reproduction, reducing yields, and diminishing production and quality. The Oryctes rhinoceros pest is known for its highly destructive capabilities, particularly in coconut plants. A safe method for controlling a rhinoceros is by employing pheromone traps. This research aims to determine the population and infestation intensity of O. rhinoceros pests. The study was conducted from June 2023 to August 2023 in Jati Mulya Village, Wonosari Subdistrict, Boalemo Regency, Gorontalo Province, using a survey method with a census technique (collecting data comprehensively) through direct field observations. The results indicate that the highest trapped population of O. rhinoceros occurred in the first week, with ten individuals, while the lowest capture was recorded in the eleventh week. The average intensity of O. rhinoceros pest infestation was 17.85%. This infestation intensity falls into the category of mild attacks.